Analysis of Law Enforcement Regarding Fault in Defamation Crimes Through Electronic Media - Diah Pudjiastuti; Sahat Maruli Tua Situmeang (Research Synergy Foundation Press, 2026)
This research investigates the enforcement of defamation laws in electronic media, focusing on the interpretation of